PENGARUH MINAT LITERASI TERHADAP HAMBATAN MEMBACA PESERTA DIDIK - Ervita Azizah; Lidya Talitha; Risyafa Andoko; Nadia Luthfiah Zahroo; Nurdiyah Kurniati; Muhammad Prayogo (STKIP Subang, 2026)
Reading difficulties are still commonly found among elementary school students, including difficulties in understanding texts, recognizing words, and reading sentences accurately. This condition is presumed to be related to students’ literacy interest. This study employed a quantitative approach with an ex-post facto design to analyze the effect of literacy interest on the reading difficulties of second-grade students at SD Negeri 003 Samarinda Utara. The participants consisted of 24 students selected using purposive sampling. Data were collected through questionnaires, observations, and documentation, then analyzed using simple linear regression assisted by SPSS. The results showed that literacy interest had a significant effect on reading difficulties with a significance value of 0.000 < 0.05 and a coefficient of determination of 0.694. The findings indicate that students who are more active in literacy activities tend to have their reading difficulties more easily identified during the learning process. Therefore, literacy interest is associated with students’ reading difficulties in elementary school.